How Can Economic Policy Strike a Balance between Economic Efficiency and Income Equality? - Assar Lindbeck (The Research Institute of Industrial Economics (IUI), 1998)
Can income equality be combined with high economic efficiency and rapid economic growth? Fortunately, we need not to answer such a general question. Indeed, the question is poorly phrased. The relationship between income and wealth distribution, on one hand, and efficiency/growth, on the other, depends on how a certain distribution of income and wealth has come about.
Keywords: E20; E25; O47; 330; Income; Economic growth; Wealth; Wirtschaftspolitisches Ziel; Wirtschaftliche Effizienz; Einkommensumverteilung; Verteilungsgerechtigkeit